The Effect of Audit Tenure and Size of Public Accountant Firm on Audit Report Lag with Auditor Industry Specialization as Moderating Variable - Haugesti Diana; Dina Hidayat (Global Writing Academica Researching and Publishing, 2022)
Relevance is one of the qualitative qualities of financial statements. If financial statements are submitted on time, they can be considered relevant. Audit report lag is closely related to timely report submission. It can increase the efficiency and quality of financial reports and enable users to rely on financial statement information when making judgments. The amount of enterprises still filing financial reports late demonstrates that punctuality remains a serious hurdle for Indonesian businesses. In contrast to earlier research, this study examines all manufacturing businesses listed on the Indonesia Stock Exchange between 2015 and 2019 using Multiple Linear Regression Analysis and Moderated Regression Analysis. The results of the study indicate that tenure audit has a significant impact on audit report lag, that the size of a public accounting firm has no significant impact on audit report lag, and that auditor industry specialization significantly moderates the impact of tenure audit and the scope of general accounting firm on audit report lag.